Myocardial scar burden predicts survival benefit with implantable cardioverter defibrillator implantation in patients with severe ischaemic cardiomyopathy: influence of gender. Issue 3 (31st October 2013) - Kwon, Deborah H; Hachamovitch, Rory; Adeniyi, Aderonke; Nutter, Benjamin; Popovic, Zoran B; Wilkoff, Bruce L; Desai, Milind Y; Flamm, Scott D; Marwick, Thomas
Abstract : Objective: We sought to assess the impact of myocardial scar burden (MSB) on the association between implantable cardioverter defibrillator (ICD) implantation and mortality in patients with ischaemic cardiomyopathy (ICM) and left ventricular EF ≤40%. In addition, we sought to determine the impact of gender on survival benefit with ICD implantation. Design: Retrospective observational study. Setting: Single US tertiary care centre. Patients: Consecutive patients with significant ICM who underwent delayed hyperenhancement-MRI between 2002 and 2006. Interventions: ICD implantation. Main outcome measures: All-cause mortality and cardiac transplantation. Results: Follow-up of 450 consecutive patients, over a mean of 5.8 years, identified 186 deaths. Cox proportional hazard modelling was used to evaluate associations among MSB, gender and ICD with respect to all-cause death as the primary endpoint. ICDs were implanted in 163 (36%) patients. On multivariable analysis, Scar% (χ 2 28.21, p<0.001), Gender (χ 2 12.39, p=0.015) and ICD (χ 2 9.57, p=0.022) were independent predictors of mortality after adjusting for multiple parameters. An interaction between MSB×ICD (χ 2 9.47, p=0.009) demonstrated significant differential survival with ICD based on MSB severity. Additionally, Scar%×ICD×Gender (χ 2 6.18, p=0.048) suggested that men with larger MSB had significant survival benefit with ICD, but men with smaller MSB derived limited benefit with ICD implantation. However, the inverse relationship was found in women. Conclusions: MSB is a powerful independent predictor of mortality in patients with and without ICD implantation. In addition, MSB may predict gender-based significant differences in survival benefit from ICDs in patients with severe ICM.